Empowering SMEs through Cultural Heritage and Clustering: Insights from Jambi Province - Lubis, Tona Aurora; Machpudin, Asep; Eka Putra, Wirmie; Ningsih, Maryati (Journal of Social Science and Business Studies, 2025)
This study examines the impact of local wisdom and clustering strategies on the performance of Micro, Small, and Medium Enterprises (SMEs) in Jambi Province. Using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), this research analyzes data collected from SMEs to identify key factors that influence their performance. The findings reveal that local wisdom, characterized by the integration of cultural and traditional values into business practices, has a positive and significant effect on SMEs performance. Among the indicators, Traditional Craftsmanship (TK) emerges as the most dominant, highlighting its role in enhancing the uniqueness and marketability of SMEs. Similarly, clustering strategies are found to significantly improve SMEs performance, with Competitiveness (DS) identified as the most influential indicator. Clustering enables SMEs to optimize resources, foster innovation, and strengthen their market competitiveness. These results underscore the importance of leveraging both cultural heritage and organizational strategies to create sustainable and competitive SME ecosystems. The implications of this study are twofold. Theoretically, it validates the integration of cultural and structural approaches in SME development. Practically, it provides actionable insights for policymakers and stakeholders to support initiatives that promote local wisdom and cluster-based strategies.